BOOK REVIEW OF NOVEL CARRIE BY STEPHEN KING - Wicaksono, Brian (LANTERN (Journal on English Language, Culture and Literature), 2015)
Human is essentially a social being. They cannot live alone, in other words, a human needs other humans. They socialize with each other, establish strong relationship and produce a harmonious society. Social humans are naturally able to communicate well with the surrounding environment as well as humans are influenced by the environment itself. Therefore, as a social being, humans are united in a society to respect other humans with various backgrounds.